Atomic-scale dispersed copper and cobalt bimetallic catalyst as well as preparation and application thereof

The atomic dispersed Cu-Co bimetallic catalyst prepared by high-temperature pyrolysis solves the problem of low nitrate removal rate and many nitrite by-products when electrochemical reduction of nitrate, and achieves the effect of efficient conversion of nitrate to ammonia nitrogen.

CN119530863APending Publication Date: 2025-02-28SHENYANG UNIV OF TECH LANJIN ENVIRONMENTAL PROTECTION IND TECH RES INST CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411652624.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the prior art, when electrochemical reduction of nitrates, the nitrate removal rate is not high and more toxic by-products are produced, and bimetallic material catalysts do not perform well in this field.

Method used

Atomically dispersed copper and cobalt bimetallic catalysts (Cu-Co-N-C) were prepared by high-temperature pyrolysis method, and Cu and Co were anchored through carbon and nitrogen co-coordination structures to form atomically dispersed bimetallic catalysts, which were applied in nitrate electroreduction reaction.

Benefits of technology

The formation of nitrite is significantly reduced, the conversion rate of nitrate and ammonia nitrogen are improved, and the stability and reaction rate of the catalyst are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530863A_ABST
    Figure CN119530863A_ABST
Patent Text Reader

Abstract

The invention relates to electrochemical treatment of nitrate wastewater, in particular to a preparation method and application of an atomic-scale dispersed copper and cobalt bimetallic catalyst. Comprising the following steps of (1) a Cu precursor preparation method, (2) a Co precursor preparation method, (3) high-temperature pyrolysis and (4) a redundant metal component removal method. The atomic-scale dispersed copper and cobalt bimetallic catalyst disclosed by the invention has relatively high metal loading capacity and relatively high stability. When the Cu-Co-N-C catalyst is applied to the nitrate electroreduction reaction, the toxic by-product nitrite is obviously reduced, the conversion rate of nitrate is obviously improved, and the ammonia nitrogen selectivity is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to electrochemical treatment of nitrate wastewater, and in particular to a preparation method and application of an atomic-level dispersed copper and cobalt bimetallic catalyst. Background Art

[0002] The treatment of high-concentration nitrate wastewater is one of the main problems in current water pollution control. Converting nitrate in wastewater into ammonia with utilization value is a feasible technical route and has become a current research hotspot. Electrochemical reduction technology can be operated at room temperature and pressure, is extremely simple to control, and does not require the addition of additional reducing agents. It has broad application prospects in the field of reducing nitrate to produce ammonia. Since copper (Cu) materials have good conductivity and strong corrosion resistance, and the adsorption energy of copper elements for nitrate ions is less than its adsorption energy for hydrogen, that is, it is difficult for hydrogen evolution side reactions to occur on the copper surface, thereby improving the reduction efficiency of copper to nitrate, making copper a widely used metal element in the field of electrochemical reduction of nitrate to produce ammonia. However, the nitrate removal rate of monometallic copper is not high during the electrochemical reduction of nitrate and a large amount of toxic nitrite byproducts are produced. Bimetallic materials have excellent electrochemical reduction of nitrate to produce ammonia performance and are a type of selectable catalyst. The adsorption energy of cobalt (Co) on nitrate is greater than that of copper. Literature reports that cobalt has a high reduction activity on nitrite. Therefore, the addition of cobalt is expected to promote the further reduction of byproduct nitrite and reduce the generation of byproducts. Consider reducing the bimetallic catalyst particles to the atomic level, taking advantage of its rapidly increased surface free energy, quantum size effect, and highly unsaturated coordinated metal atomic sites, to construct atomically dispersed Cu-Co bimetallic catalysts, so as to further improve the reaction rate and ammonia nitrogen generation rate of bimetallic catalysts in reducing nitrate to ammonia. Summary of the invention

[0003] The present invention constructs an atomic-level dispersed Cu-Co bimetallic catalyst to further improve the reaction rate and ammonia nitrogen generation rate of the bimetallic catalyst in reducing nitrate to produce ammonia.

[0004] (1) High-temperature pyrolysis was used to anchor Cu and Co with a carbon-nitrogen (C, N) co-coordination structure to form an atomically dispersed bimetallic catalyst (Cu-Co-NC).

[0005] (2) When the Cu-Co-NC catalyst is used in the nitrate electroreduction reaction, the catalyst structure can be stabilized and the toxic byproduct nitrite can be significantly reduced, which is beneficial to the efficient conversion of nitrate and its highly selective reduction to ammonia nitrogen.

[0006] Specifically, it is an atomically dispersed copper and cobalt bimetallic catalyst, in which copper atoms and cobalt atoms are atomically dispersed and anchored on the N-doped C structure. The catalyst maintains the original structure and morphology of the N-doped C, and the total loading of copper atoms and cobalt atoms is more than 13.78wt.%.

[0007] (2) A method for preparing an atomically dispersed copper and cobalt bimetallic catalyst is provided, comprising the following steps:

[0008] 1) Preparation method of Cu precursor

[0009] ① Dissolve trimesic acid in ethanol and ultrapure water in a volume ratio of 1:1, and stir thoroughly until dissolved to form solution 1;

[0010] ② Prepare an aqueous solution containing copper acetate monohydrate and L-glutamic acid, i.e., solution 2; fully mix solution 1 and solution 2, and stir continuously until flocs are precipitated, and use a suction filtration device to perform repeated operations of suction filtration-rinsing-suction filtration for multiple times. The obtained filter cake is vacuum dried in a vacuum drying oven at 60°C overnight.

[0011] 2) Preparation method of Co precursor

[0012] ① Dissolve trimesic acid in ethanol and ultrapure water in a volume ratio of 1:1, and stir thoroughly until dissolved to form solution 1;

[0013] ② Prepare an aqueous solution containing cobalt chloride hexahydrate and L-glutamic acid, i.e., solution 2; mix solution 1 and solution 2 and stir them fully until flocs are precipitated, and use a suction filtration device to perform repeated operations of suction filtration-rinsing-suction filtration for multiple times. The obtained filter cake is vacuum dried in a vacuum drying oven at 60°C overnight.

[0014] 3) High temperature pyrolysis

[0015] The Cu precursor and the Co precursor are mixed in a certain proportion to obtain a mixture 1, the mixture 1 is fully mixed and ground with dicyandiamide, a certain amount of the mixture is put into a quartz boat, and placed in a vacuum tube furnace for heat treatment. The vacuum tube furnace is evacuated and filled with nitrogen for three cycles before heating. The heat treatment temperature is set according to different parameter conditions, the heating rate is 3-5℃ / min, and the temperature is kept at the highest temperature for more than 3h, and finally the temperature is naturally cooled to room temperature under nitrogen.

[0016] 4) Method for removing excess metal components

[0017] The pyrolyzed catalyst sample is placed in a dilute hydrochloric acid solution and stirred thoroughly to remove excess metal single substance components in the sample.

[0018] (3) Provide the application of the atomically dispersed copper and cobalt bimetallic catalyst in the field of electrochemical reduction of nitrate to produce ammonia.

[0019] Beneficial effects of the present invention:

[0020] (1) The present invention obtains a novel atomic-level dispersed Cu-Co bimetallic catalyst with co-coordination of C and N by high-temperature pyrolysis. In the preparation process, two metal precursors are formed by highly coordinating two metal salts with a carbon source respectively, and the two metal precursors are directly mixed with a nitrogen source for one-step pyrolysis. Compared with the method of first obtaining a carrier and then loading metal atoms, the steps are greatly simplified.

[0021] (2) The atomically dispersed Cu-Co bimetallic catalyst prepared by high-temperature pyrolysis has a high metal loading and high stability.

[0022] (3) When Cu-Co-NC catalyst is used in nitrate electroreduction reaction, the toxic byproduct nitrite is significantly reduced, the conversion rate of nitrate is significantly increased, and the selectivity of ammonia nitrogen is significantly increased. Compared with Cu-NC catalyst, the addition of Co element reduces the generation rate of byproduct nitrite by Cu-Co-NC catalyst by 88.03%, and NH 4 + -N generation rate increased by 7.67%. Higher concentration of NO 3 - NO2 over atomically dispersed Cu-Co-NC catalysts under -N (200 mg / L) conditions 3 - -N removal rate is 20.13% higher than that of the flat Cu-Co bimetallic electrode, and NH 4 + -N generation rate increased by 1.2 times, NH 4 + The -N selectivity was increased by 83.91%. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Schematic diagram of the preparation process of atomically dispersed copper and cobalt bimetallic catalysts.

[0024] Figure 2 is the SEM photo of Cu-Co catalyst;

[0025] Figure 3 TEM and HRTEM images of the catalyst;

[0026] Figure 4 HAADF-STEM image of the catalyst;

[0027] Figure 5The composition and element distribution of the catalyst were obtained by EDS analysis based on HRTEM characterization; among them: a) the element distribution of C, N, Co, and Cu in HAADF mode; b) the element distribution of C, N, Co, and Cu; c) the distribution of Cu element; d) the distribution of Co element; e) the distribution of C element; f) the distribution of N element;

[0028] Figure 6 During the 10-time electrode cycle, NO 3 - -N removal rate graph;

[0029] Figure 7 During the 10-times electrode recycling process, NH 4 + -N generation rate change graph;

[0030] Figure 8 Effect of initial pH value on the electrocatalytic performance of Cu-Co-NC electrode a) NO 3 - -N removal rate variation curve over time; b) NO 2 - -N generation rate over time; c) Initial pH value and NH 4 + -The influence of N selectivity;

[0031] Fig. 9 XRD patterns of Cu-Co-NC catalysts at different heat treatment temperatures;

[0032] Fig.10 Effect of heat treatment temperature on the electrocatalytic performance of Cu-Co-NC electrode for nitrate removal a) NO 3 - -N removal rate; b) NO 2 - - Changes in N generation rate; c) NH 4 + -N generation rate change graph. DETAILED DESCRIPTION

[0033] The technical solution of the present invention is described in detail below through specific embodiments. The following embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following embodiments.

[0034] Embodiment 1:

[0035] A method for preparing an atomically dispersed copper and cobalt bimetallic catalyst is as follows:

[0036] 1) Preparation method of Cu precursor

[0037] ① Weigh 2.24 g of trimesic acid, add 100 mL of ethanol and 100 mL of ultrapure water, and stir thoroughly until dissolved to form solution 1;

[0038] ② Weigh 4 g of copper acetate monohydrate and 1.48 g / L glutamic acid respectively, dissolve in 800 mL of ultrapure water to form solution 2; fully mix solution 1 and solution 2, stir continuously for 2 h, until flocs are precipitated, use a filtration device to repeat the operation of filtration-rinsing-filtration 3 times, and vacuum dry the obtained filter cake in a vacuum drying oven at 60 ° C for 12 h.

[0039] 2) Preparation method of Co precursor

[0040] ① Weigh 2.24 g of trimesic acid, add 100 mL of ethanol and 100 mL of ultrapure water, and stir thoroughly until dissolved to form solution 1;

[0041] ② Weigh 2.529 g of cobalt chloride hexahydrate and 1.48 g of L-glutamic acid, add 800 mL of ultrapure water to form solution 2; mix solution 1 and solution 2 and stir them thoroughly for 2 h until flocs are precipitated, use a filtration device to repeat the operation of filtration-rinsing-filtration 3 times, and the obtained filter cake is vacuum dried in a vacuum drying oven at 60 ° C for 12 h.

[0042] 3) High temperature pyrolysis

[0043] The Cu precursor and the Co precursor are mixed in a mass ratio of 1:1 to obtain a mixture 1, and the mixture 1 and dicyandiamide are fully mixed and ground in a mass ratio of 1:15. 1 g of the mixture is placed in a quartz boat and placed in a vacuum tube furnace for heat treatment. The vacuum tube furnace is subjected to three reciprocating cycles of evacuation and nitrogen filling before heating. Under nitrogen protection, the heat treatment temperature is set according to different parameter conditions, the heating rate is 3°C / min, and the maximum temperature of 700°C is maintained for 3 hours, and finally the temperature is naturally reduced to room temperature under the condition of flowing nitrogen.

[0044] 4) Method for removing excess metal components

[0045] The pyrolyzed catalyst sample was placed in 200 mL of 5% hydrochloric acid solution and stirred for 5 hours to remove the excess metal element components in the sample. Finally, the desired catalyst Cu-Co-NC was obtained, with a metal loading of 13.78 wt.%, and a mass fraction ratio of copper to cobalt of 51.3:100.

[0046] Figure 2This is a SEM photo of a Cu-Co catalyst. It can be observed that the catalyst surface has high roughness, uniform light and dark distribution, good metal dispersion, and is easy to form an atomically dispersed catalyst, which may have high catalytic activity.

[0047] Figure 3 The catalyst was characterized by transmission electron microscopy (TEM), high-resolution transmission electron microscopy (HRTEM) and spherical aberration-corrected high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM). Figure 3 shown. Figure 3 a) shows the TEM image of the catalyst, from which it can be observed that the catalyst has a flaky structure with good uniformity and dispersion, and no aggregation of metal particles occurs. The catalyst was characterized using HRTEM with higher resolution ( Figure 3 b), almost no high-contrast crystalline nano (or micro) particles can be observed in the figure, and the catalyst is mainly composed of amorphous carbon.

[0048] Figure 4 The HAADF-STEM image of the catalyst shows that a large number of small bright spots with high contrast are observed in the 5nm scale field of view, indicating that the metal has good dispersion on the nitrogen-doped carbon support of the catalyst. No metal clusters of Cu and Co are observed in different regions, indicating that an atomically dispersed catalyst has been successfully prepared. These small bright spots are atomically dispersed Cu and Co metals. The small circles in the figure mark the atomic pairs that are close to each other and composed of bright spots. They may be atomic pairs of Cu and Co or Cu atomic pairs or Co atomic pairs. This is attributed to the similar atomic numbers of Cu and Co and the similar brightness of the spots of atomic pairs in the HAADF mode. In summary, the present invention obtains an atomically dispersed Cu-Co bimetallic catalyst.

[0049] Figure 5 The EDS analysis based on HRTEM characterization is used to determine the composition and element distribution of the catalyst. The results show that the four elements C, N, Cu and Co in the catalyst are evenly distributed, which can be determined Figure 4 The small bright spots scattered in the image are Cu and Co atoms.

[0050] The atomically dispersed Cu-Co bimetallic catalyst (Cu-Co-NC) prepared above is formed into an electrode, and the electrode is applied to the process of electrochemical reduction of nitrate to produce ammonia.

[0051] The electrode forming method is as follows:

[0052] Prepare a mixed solution of 1 mL ethanol and 1 mL ultrapure water, add 10 mg of the above catalyst to the mixed solution, shake well, and disperse by ultrasonic for 2 min, add 100 μL Nafion solution (5 wt.%) to the above solution, shake well, and ultrasonic for 1 h to form a uniform dispersion. Add 80 μL of the dispersion dropwise onto the surface of the carbon cloth (one side) with a length × width = 1 cm × 1.5 cm, completely wet and disperse it, and then dry it naturally to form an electrode.

[0053] The constant current electroreduction experiment of nitrate was carried out in a single-chamber reactor, with a graphite electrode as the anode and an electrode formed by the above catalyst as the cathode, and the electrode spacing was 1.0 cm. The experimental conditions were: 100 mg / L NaNO 3 (in terms of N) and 0.25 mol / LNa 2 SO 4 The current density applied between the anode and cathode is 25 mA / cm 2 , the initial pH value of the aqueous solution was 6.0, and the operation was carried out for 6 hours.

[0054] The above-mentioned constant current electroreduction process of nitrate was repeated 9 times by replacing the aqueous solution (the cathode electrode was recycled for a total of 10 times);

[0055] Figure 6 , Figure 7 During the 10-times electrode cycle (6 h each electrolysis), NO 3 - -N removal rate and NH 4 + The results show that the electrode material is a stable material with excellent electrochemical activity. After repeating the nitrate reduction experiment 10 times, its activity remains almost unchanged. 3 - -N removal rate and NH 4 + -N generation rates have only slight disordered fluctuations, which are about 98.62% and 73.00%, respectively, indicating that the Cu-Co-NC electrode material has good reusability.

[0056] Table 1 shows the comparison of the electrocatalytic reduction of nitrate by the Cu-Co-NC electrode materials in this paper and other electrode materials reported in the literature. Compared with the Cu-NC single metal electrode, the atomically dispersed Cu-Co-NC bimetallic electrode has a higher NO 3 - -N removal rate and NH 4 + -N has a higher generation rate, NO 2 --N generation rate is low, and the addition of Co element significantly reduces the production of byproduct nitrite. Compared with the electrode materials for catalyzing nitrate to ammonia production reported in other literature, the atomically dispersed Cu-Co-NC bimetallic electrode material prepared in this paper effectively shortens the reaction time and increases the nitrate reduction reaction rate, and has obvious advantages in nitrate removal, ammonia nitrogen generation and reduction of nitrite byproducts. It further highlights the effect of the addition of Co element on the performance of Cu-Co-NC electrode catalyzing nitrate to ammonia production. This atomically dispersed Cu-Co bimetallic electrode has application prospects in the field of electrochemical catalytic reduction of nitrate to ammonia production.

[0057] Table 1 Comparison of electrocatalytic nitrate performance of Cu-Co-NC electrode and other electrodes

[0058]

[0059] The Cu-NC catalyst is prepared by mixing the Cu precursor of the present invention (obtained in step 1 of Example 1) with dicyandiamide (mass ratio 1:15) through the above-mentioned high-temperature pyrolysis method (step 3 of Example 1)).

[0060] [1] Zhao X, Li

[0061] [2] Zhu T, Chen Q, Liao P, et al. Single-atom Cu catalysts for enhanced electrocatalytic nitrate reduction with significant alleviation of nitrite production [J]. Small, 2020, 16(49): 1-10.

[0062] [3]Xue Y, Yu Q, Ma Q, et al. Electrocatalytic hydrogenation boostsreduction of nitrate to ammonia over single-atom Cu with Cu(I)-N 3 C 1 sites[J].Environmental Science&Technology,2022,56(20):14797-14807.

[0063] Example 2

[0064] The process and conditions are the same as in Example 1, except that the initial pH value of the solution during the electrochemical reduction of nitrate is different.

[0065] Application results: Under different initial pH conditions, the electrochemical catalytic reduction of nitrate by Cu-Co-NC electrode produces NO 3 - -N removal rate, NO 2 - -N generation rate, NH 4 + -N generation rate and NH 4 + -N selectivity changes over time Figure 8 As shown. Figure 8 It can be seen from a) that the Cu-Co-NC electrode generally has a good removal effect on nitrate wastewater with different initial pH values. Figure 8 b) shows that after 6 h of reaction, the NO 2 - -N generation rates are all at a low level. Figure 8 c) shows that the electrode reacts with NH 4 + The selectivity of -N is as high as 89.18%

[0066] The excellent performance of the electrode under acidic conditions is highly matched with the pickling wastewater treatment conditions of metal processing, which shows that the electrode has strong practicality.

[0067] Example 3

[0068] The process and conditions are the same as those in Example 1, except that a different heat treatment temperature is used to prepare the catalyst.

[0069] Application results: The crystal structure characterization results of electrode materials at different heat treatment temperatures are as follows: Fig. 9For the NC catalyst without metal loading, an obvious diffraction peak appeared at about 26.3° in its XRD pattern. After comparison with the standard card PDF#01-0640, the diffraction peak was C(002

[0070] ). For the catalysts heat treated at 700℃, 800℃, 900℃ and 1000℃, the diffraction peak of C(002) appeared at about 26.3°, indicating that the catalysts prepared at these temperatures maintained the original NC main structure. For the catalyst prepared at 600℃, an obvious diffraction peak appeared at about 27.2° in its XRD pattern. After comparison with the standard card PDF#31-1938, the diffraction peak was C 5 H 6 N 2 O 2 The diffraction peak of (120) indicates that the sample is not completely carbonized under the heat treatment condition of 600℃, and the two elements H and O still exist, resulting in the color of the catalyst sample being yellowish. The catalyst samples obtained under other high temperature conditions are black, which is exactly the same as the SEM analysis. The XRD pattern was analyzed using jade software. When the heat treatment temperature was 800℃, the

[0071] Under the conditions of 900℃ and 1000℃, the catalyst showed three diffraction peaks at 44.2°, 51.5° and 75.8° respectively. After comparing with the standard card PDF#15-0806, these three diffraction peaks correspond to Co(111), Co(200) and Co(220), which indicates that a small amount of clusters may appear in the Co metal in the catalyst under high temperature conditions, reducing the atomic utilization rate. For the catalyst obtained under the heat treatment condition of 700℃, there is only the diffraction peak of amorphous carbon in its XRD pattern. In summary, the catalyst obtained under the heat treatment condition of 700℃ may be an atomic-level dispersed structure.

[0072] Cu-Co-NC electrodes with different heat treatment temperatures for NO electrocatalysis in the nitrate process 3 - -N removal rate, NO 2 - -N generation rate, NH 4 + -N generation rate and NH 4 + -N selectivity changes such as Fig.10 When the heat treatment temperature is 700℃, the electrochemical reduction of nitrate to produce ammonia is the best. After 6h of reaction, NO 3 - -N removal rate was 98.52%, NO 2 - -N generation rate is 0.34%, NH4 + The -N generation rate was 73.00%, which may be related to the atomic structure of the catalyst obtained under the heat treatment condition of 700℃.

Claims

1. A method for preparing an atomically dispersed copper and cobalt bimetallic catalyst, characterized in that: The steps include: 1) Preparation method of Cu precursor ① Dissolve trimesic acid in ethanol and water in a volume ratio of 0.95:1-1.05:1 (preferably 1:1), stir thoroughly until dissolved, and form a solution 1; the mass concentration of trimesic acid in the solution 1 is 10.64-11.76 g / L (preferably 11.2 g / L); ②Prepare an aqueous solution containing copper acetate and L-glutamic acid, i.e., solution 2; the mass concentration of copper acetate therein is 4.75-5.25 g / L (preferably 5 g / L); the mass ratio of copper acetate to L-glutamic acid is 2.57:1-2.84:1 (preferably 2.70:1); Mixing solution 1 and solution 2 in a volume ratio of 1:3.81-1:4.21 (preferably 1:4), stirring until flocs are precipitated, separating the solid and the liquid, and drying the solid to obtain a Cu precursor; 2) Preparation method of Co precursor ① Dissolve trimesic acid in ethanol and water in a volume ratio of 0.95:1-1.05:1 (preferably 1:1), stir thoroughly until dissolved, and form a solution 1; the mass concentration of trimesic acid in the solution 1 is 10.64-11.76 g / L (preferably 11.2 g / L); ②Prepare an aqueous solution containing cobalt chloride and L-glutamic acid, i.e., solution 2; the mass concentration of cobalt chloride therein is 3.003-3.319 g / L (preferably 3.161 g / L); the mass ratio of cobalt chloride to L-glutamic acid is 1.62:1-1.79:1 (preferably 1.71:1); Mixing solution 1 and solution 2 in a volume ratio of 1:3.81-1:4.21 (preferably 1:4), stirring until flocs are precipitated, separating the solid and the liquid, and drying the solid to obtain a Co precursor; 3) High temperature pyrolysis: The Cu precursor and the Co precursor are mixed in a mass ratio of 0.1:1-9:1 (preferably 1:1) to obtain a mixture 1, and the mixture 1 is mixed and ground with dicyandiamide to obtain a mixture, wherein the mass ratio of the mixture 1 to dicyandiamide is 1:5-1:20 (preferably 1:15); The mixture is heat treated under inert atmosphere protection, with the highest temperature being 650-750° C. (preferably 700° C.), reaching the highest temperature after 2.1-4.1 hours (preferably 3.5-3.9 hours), and kept warm for 3-4 hours (preferably 3 hours); 4) Method for removing excess metal components The pyrolyzed sample is soaked in a dilute hydrochloric acid solution to obtain the desired catalyst.

2. The preparation method according to claim 1, characterized in that: The heating rate of the heat treatment process from room temperature to the treatment temperature in step (3) is 3-5°C / min; The inert atmosphere gas is one or both of nitrogen and argon.

3. The preparation method according to claim 1, characterized in that: Step (4) The mass fraction of dilute hydrochloric acid is 4%-10% (preferably 5%-6%), and the mixture is soaked and stirred for 4h-8h (preferably 5-6h).

4. A copper-cobalt bimetallic catalyst prepared by the preparation method according to any one of claims 1 to 3.

5. The preparation method according to claim 1, characterized in that: Atomically dispersed copper and cobalt bimetallic catalysts have copper and cobalt atoms atomically dispersed and anchored on the N-doped C structure; The catalyst has a flaky structure, high surface roughness, good uniformity and dispersion, and no aggregation of metal particles occurs; copper and cobalt metals exist in the form of atoms; The metal loading of the catalyst is 7.35-13.78wt.%, and the mass fraction ratio of the copper element to the cobalt element is 7.5:100-51.3:

100.

6. Use of the copper and cobalt bimetallic catalyst according to claim 4 in the process of electrochemical reduction of nitrates to produce ammonia.

7. The preparation method according to claim 6, characterized in that: The copper and cobalt bimetallic catalyst is used as a cathode active component, and an electrode made of the copper and cobalt bimetallic catalyst can be used as a cathode in the process of electrochemical reduction of nitrate to produce ammonia.

8. The preparation method according to claim 6, characterized in that: The electrode refers to an electrode composed of a conductive substrate with a copper and cobalt bimetallic catalyst attached to the surface; The conductive substrate is one or more of carbon cloth and carbon paper.

9. The preparation method according to any one of claims 6 to 8, characterized in that: Electroreduction of nitrate: The composition of the nitrate solution is an aqueous solution of 20-1000 mg / L NaNO3 (in terms of N) (preferably 50-300 mg / L) and 0.25 mol / L Na2SO4, and the initial pH value of the aqueous solution is 2-12; The anode is one or more of graphite electrode, carbon felt, and carbon fiber, and the cathode is an electrode formed by the above catalyst. The current density applied between the anode and the cathode is 10-30 mA / cm 2 (Preferably 20-30 mA / cm 2 ).

Citation Information

Cited By

  • Co-Cu / rGO-Ti electrode and preparation method and application thereof

    CN120463295A